The Role Of Promotion In Mediation Of Lifestyle And Product Quality On Buying Interest Yamaha NMAX Motorcycles - Suleman, Dede; Suyoto, Yohanes Totok; Zahra, Zahra; Sari, Imelda; Lestiningsih, Amin Setio; Yulistria, Resti; Widyastuti, Indria; Haryati, Raden Ati (IJOSMAS, 2022)
The purpose of this study was to examine and analyze the effect of lifestyle and product quality on interest in buying Yamaha NMAX motorcycles with promotion as a mediating variable. Data were collected through questionnaires to 55 respondents who owned Yamaha NMAX motorcycles in Jakarta, data collection used purposive sampling technique. The collected data is processed by using the Structural Equation Model (SEM) analysis method with the SmartPLS 3.0 software tool. The results show that lifestyle has a significant effect on promotion and buying interest, product quality has a significant effect on promotion and buying interest, promotion does not significantly affect buying interest, promotion is not a good mediating variable on buying interest.